A model for total volume of debris flow with intermittent surges based on maximum peak discharge and movement time. Issue 4 (4th July 2017) - Li, Jun; Chen, Ningsheng; Wang, Tao; Iqbal, Javed; Xiang, Long
Abstract: A total volume of debris flow with intermittent surges is an important design parameter for the prevention of debris flow which requires an accurate determination of total volume of debris flow. Firstly, based on the data of 63 debris flow events from 1987 to 1995 at Jiangjia gully in Dongchuan County, Yunnan Province, China, we find that the distribution of debris flow discharge can be described by the lognormal distribution. Secondly, a statistical model for the total volume of debris flow with intermittent surges is established by the most stable fractile and the lognormal distribution function. Thirdly, we verified the accuracy of Equation (15) using data of 65 debris flows events from 1996 to 2004 in Jiangjia gully. Equation (15) generated more accurate results when compared with other existing models. The results of research are as follows: The Average Relative Error and Sum of Squared Relative Errors of Equation (15) are 47.6%p and 22.3, which is 10.9%p and 8.0 lower than that of Ou model, respectively. This model can be better applied to calculate the total volume of debris flows with intermittent surges in Jiangjia gully.